Pertanggungjawaban Pidana Terhadap Pelaku Penipuan Investasi Online Berdasarkan Kitab Undang-Undang Hukum Pidana - Tedy Kuswoyo; Wawan Kurniawan; Oktariansyah Fresky Fralesta, Muhammad Reza; Septian Dewa Pratama; Kinaria Afriani (Consensus : Jurnal Ilmu Hukum, 2022)
With information technology, people can interact with each other almost without national or regional boundaries. This increases mobility. It is hoped that these various conveniences will improve the welfare and progress of Indonesian society. Due to the rapid and limitless progress of technology and information, the behavior of society and human civilization will certainly change throughout the world. This also causes the emergence of online fraud. People who use the internet for business and trade purposes so that they no longer rely on real business operations commit online fraud. Investment is one of the online frauds. Investment offer sites offer high interest profits, etc. Online fraud must meet all criminal requirements and be able to prove that it was done in a conscious state. To determine who is responsible for the crime of online fraud, special penalties must be applied. This is because law enforcement must understand the breadth of evidence sources to avoid misinterpretation and ensure that everyone understands the power of proof in the same way.